Improving opportunities for data linkage within Children Looked After administrative records in Wales - Grace Bailey; Alex Lee; Saira Ahmed; Ieuan Scanlon; Laura Cowley; Amy Stuart; Ian Farr; Caroline Brooks; Laura North; Lucy Griffiths (International Journal of Population Data Science, 2025)
Introduction Linkage of population-based administrative data is a powerful tool for studying important public issues. To overcome confidentiality and disclosure issues, records are de-identified and allocated a unique identifier. Within the Secure Anonymised Information Linkage (SAIL) Databank, these are known as Anonymised Linking Fields (ALFs). Assignment of an ALF enables linkage of individuals across multiple routinely collected datasets. Within the Children Looked After (CLA) Wales dataset, only 37% of the children have an ALF, limiting linkage to other datasets and, as a result, potential research. There are also other known data issues, including discrepancies with the week of births, duplicate identifiers and year-on-year changes in identifiers.